Fathers' psychological responses to pediatric cancer–induced financial distress. Issue 6 (11th April 2020) - Santacroce, Sheila Judge; Killela, Mary K.; Kerr, Gavin; Leckey, Jill A.; Kneipp, Shawn M.
Abstract: Background: To describe how pediatric cancer–induced financial distress and perceptions of their social role affected fathers' psychological responses to this distress, and quality of life (QOL) for them and their families. Procedure: We analyzed father‐only responses from a larger cross‐sectional survey study about the impact of pediatric cancer–induced financial distress on parents. Our analytic sample was n = 87 fathers who participated in the larger study. We analyzed their data using descriptive statistics and directed content analysis. Results: Conflicting role responsibilities (be there for child; work to maintain income and insurance coverage) seemed to generate responses resembling characteristic posttraumatic stress symptoms in reaction to acute declines in family finances and/or the chronic stress of insufficient finances to meet financial demands, that is, financial trauma. Fathers' personal sense of not being able to adequately provide for their child with cancer and also meet their family's basic needs produced embarrassment and humiliation, which led to discomfort talking about finances; fear, persistent thoughts and anxiety about money; reduced joy; beliefs that they did not deserve to express their needs; and feeling vulnerable to repeated financial stressors. Conclusions: Pediatric cancer–induced financial burden contributed to fathers' symptom severity and burden, and QOL declines. Clinicians should develop sensitivity to the multiple ways that pediatric cancer affects individuals and families. Future research should examine the effects of pediatric cancer–induced financial burden on mothers, and develop ways to sensitively and systematically assess financial burden, associated psychological responses and declines in QOL, and intervene as indicated.